Attitudes and priorities of training clinicians in diagnosing delirium in an academic hospital - (:unkn) unknown (My University, 2004)
Objective: The aim of our study is to explore the attitudes and practices of residents on establishing a diagnosis of delirium and their clinical intervention in different clinical settings in Marmara University Hospital. Methods: Seventy-five residents in different clinical settings in Marmara University Hospital completed a 14-item questionnaire which focused on their priorities and attitudes concerning diagnosis and treatment of delirium. Results: Orientation difficulties, clouding of consciousness and hallucinations were chosen as the most frequently encountered symptoms of delirium. For the purpose of establishing the etiology of delirium the most frequently preferred method was biochemical screening. Metabolic imbalances were most frequently found while only less than 50% of participants could establish the etiology. Most of the participants indicated treatment of the specific etiology as the preferred treatment method of delirium. Haloperidol was the most frequently selected medication for symptom control. Discussion: Delirium still remains an important clinical emergency in clinical practice. We hope this study will promote further insight for daily clinical routines in Marmara University Hospital. We believe this effort will provide ground for developing new consensus guidelines for the management of delirium, which will improve the outcome and treatment process of this clinical condition.
Keywords: Clinical practice; Delirium